2023
DOI: 10.1186/s13046-023-02934-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors in fibroblast plasticity and CAF heterogeneity

Roberta Melchionna,
Paola Trono,
Anna Di Carlo
et al.

Abstract: In recent years, research focused on the multifaceted landscape and functions of cancer-associated fibroblasts (CAFs) aimed to reveal their heterogeneity and identify commonalities across diverse tumors for more effective therapeutic targeting of pro-tumoral stromal microenvironment. However, a unified functional categorization of CAF subsets remains elusive, posing challenges for the development of targeted CAF therapies in clinical settings.The CAF phenotype arises from a complex interplay of signals within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 141 publications
1
1
0
Order By: Relevance
“…However, we found that the MAFs expressed SMA/A, FGF7, FAP, and PDGFR, which is partially consistent with recently published work [18]. We found heterogeneous expression of these markers, which correlates with the demonstrated heterogeneity of such cell subpopulations [34][35][36]. We were able to obtain eight mPDO cultures from twelve pleural effusions.…”
Section: Discussionsupporting
confidence: 91%
“…However, we found that the MAFs expressed SMA/A, FGF7, FAP, and PDGFR, which is partially consistent with recently published work [18]. We found heterogeneous expression of these markers, which correlates with the demonstrated heterogeneity of such cell subpopulations [34][35][36]. We were able to obtain eight mPDO cultures from twelve pleural effusions.…”
Section: Discussionsupporting
confidence: 91%
“…Activated CAFs fall into several categories defined by their function, specific markers, and transcription factors specifying the CAFs subtypes. The extensive heterogeneity in CAFs phenotypes in diverse cancers has been comprehensively reviewed ( Biffi and Tuveson, 2021 ; Plikus et al, 2021 ; Chhabra and Weeraratna, 2023 ; Melchionna et al, 2023 ). As our understanding of CAFs heterogeneity increased, different studies identified specific subsets of CAFs in various tissues (see Table 1 ).…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%